2018
DOI: 10.1007/s13760-018-0935-7
|View full text |Cite
|
Sign up to set email alerts
|

Smaller caliber of the internal carotid artery in patients with ipsilateral aplasia of the A1 segment of the anterior cerebral artery: a study with CTA

Abstract: To measure the diameter and the transsectional area of the internal carotid arteries (ICA) on CT Angiography (CTA) in patients with aplasia of the A1-segment of the ACA (A1) and in patients with symmetrical A1, the mean diameter and area of the ICA on both sides were measured at a level of 2 cm below the skull base with a commercially available CT software in 41 consecutive patients with aplasia of A1 observed during a 12-month period on CTA and in 41 control patients with symmetrical A1. The mean diameter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is a rare finding, but the most frequently observed variation of the anterior cerebral artery [37]. Lippert and Pabst indicated this variant to occur in 10% of cases [20], Carels et al found it in 10.5% [6], but Uchino et al (2006) observed it in just 5.6% of cases [37].…”
Section: Aplasia Of the A1 Segment Of The Anterior Cerebral Artery Anmentioning
confidence: 99%
“…This is a rare finding, but the most frequently observed variation of the anterior cerebral artery [37]. Lippert and Pabst indicated this variant to occur in 10% of cases [20], Carels et al found it in 10.5% [6], but Uchino et al (2006) observed it in just 5.6% of cases [37].…”
Section: Aplasia Of the A1 Segment Of The Anterior Cerebral Artery Anmentioning
confidence: 99%